Extending argoUML© for real-time UML® - Lopes, Sérgio F. (2004)
The “UML Profile for Schedulability, Performance and Time Specification” (UML-SPT) is an extension of the Unified Modeling Language™ (UML) for the real-time domain, defined by the Object Management Group™ (OMG™)i. This profile includes a model of key domain concepts that are mapped to UML in the form of stereotypes, with their respective tagged values and constraints. Software designers can annotate their application models with these UML standard extension mechanisms in order to model time-, schedulability-, and performance-related aspects. At the present time, only one tool declares support to the UML-SPT profile, however these are closed commercial Computer-Aided Software Engineering (CASE) tools from major vendors, and cannot be easily tailored to more specific ends. ArgoUMLii is an extensible platform-independent UML design tool with cognitive support, developed as an open-source project based on the Java™ programming languageiii. Extending it has the advantage of enabling further refinements to the real-time profile and also to have complete control over the application, and thus the possibility to include special features. Yet, there is no single and consistent document describing completely the implementation of a plugin/module for ArgoUML. This paper describes its extension to support the implementation of the UML-SPT profile, and presents our experience in developing the respective module, namely the difficulties faced, the discussion of different alternatives and the proposed final solutions.